PENGARUH PERAN SERTA MASYARAKAT DAN PEMBANGUNAN DESA TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA PETALING JAYA KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU - Triyono, Aris (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This research was carried out in Petaling Jaya Village, Batang cenaku, Indragiri Hulu Regency. The purpose of the study was to determine the effect of community participation and village development on public welfare in Petaling Jaya Village, Batang Cenaku, Indragiri Hulu Regency, both simultaneously and partially. This research used interview and questionnaire, and by using multiple linear regression analysis methods. The sampling method using purposive sampling method with a total sample of 75 respondents. Results: Community participation and village development have a significant effect on community welfare simultaneously, community participation (X1) has a significant effect on public welfare (Y) partially, partially the village development (X2) significantly affects the public welfare (Y), community participation and village development simultaneously has very strong and positive effect on public welfare. While based on the analysis table obtained the number R2 (R Square) or called the coefficient of determination is equal to 0.847. It means that 84.7% shows the percentage contribution of independent variables. Community participation and village development on the dependent variable of public welfare is able to explain 84.7% of the variation of the dependent variable of public welfare, while the 15.3% is influenced by other variables which wasn’t examined in this research